The Students Perception on the Use of E-Book as Learning Sources at The Sixth Semester Students of English Education Study Program of Baturaja University - Henny Yulia (Edukasi Lingua Sastra, 2021)
The purpose of this study was to find out the students perceptions on the use of e-book as learning sources at the sixth semester students of English Education Study Program of Baturaja University.The population of the research was 22 students majoring in English study program. The writer took 22 students by using total sampling.This study used descriptive qualitative method and the data was collected by using questionaire. The questionnaire consists of 20 items in the form of five likert scale. The result of the study showed that 92.90% students had positive response and support e book as learning sources. It indicated that e book was easy to use. By using e book the both students and lecturers can improve their creativity.